Following the crowd? Peer influence on voluntary bank audits - Beck, Matthew J.; Lundstrom, Nathan G.; Stuber, Sarah B. (Contemporary Accounting Research, 2024)
Abstract We examine whether peer audit choices influence a bank's decision to obtain an audit voluntarily. We find that the likelihood of a bank voluntarily obtaining an audit is significantly associated with the audit decisions of peers. The relation is stronger when the peers are more salient due to closer geographic proximity, similarity in loan portfolio, and similarity in size. In addition, we find that peer influence on a bank's audit decision is moderated by the bank's existing level of assurance. Specifically, banks already obtaining a lower level of assurance are less likely to begin an audit in response to peer influence. We also find no evidence that peer influence extends to banks' decisions to cease obtaining an audit. Overall, our findings are consistent with peer influence significantly influencing banks' decisions to begin obtaining an audit.